Mitoprotective effect of the receptor antagonist interleukin-1 in experimental cerebral stroke - E. V. Suprun (Patologìâ)
Mitoprotective activity of the receptor antagonist of interleukin-1 ( RAIL-1, 7,5 mg/kg) comparing to Thiotriazoline (50 mg/kg) was studied on the model of experimental photoinduced cerebral thrombosis in rats. Against a background of RAIL-1 administration significant stabilization of mitochondria functional activity was noted (by blocking of mitochondrial pore opening) as wel as the state of thiol-disulfide system: normalization of activity of glutationperoxidase and glutationreductase, increase of levels of reduced forms of glutathione and thiols against a background of reduction of their oxidized forms. By mitochondrial activity RAIL-1 can be compared to Thiotriazoline and even exceeds it in some parameters.